ETIOLOGY AND RISK FACTORS FOR NEONATAL ADMISSION WITH RESPIRATORY DISTRESS: A TERTIARY CARE HOSPITAL-BASED STUDY - Nazir, Tariq; Khan, Rifat; Lone, Rais Ahmad; Nazir, Shaista (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Respiratory disorders are the most common cause of admission for neonatal intensive care unit whose incidence ranges from 4% in term babies and 20% in post-terms to 30% in pre-terms. The incidence increases with decreasing gestational age and birth weight. Severity of distress is assessed by scoring systems. There is no study conducted in this tertiary center; for this reason, we took this study to identify the etiology and risk factors for neonates admitted. Methods: This was a hospital-based prospective study done at a tertiary care center in NICU of GB Pant hospital, Srinagar, for a period of 6 months between January 2020 and June 2020. A total of 320 babies were taken up for the study with 187 (58.4%) male and 133 (41.6%) female babies. Respiratory distress was defined as having any two signs of respiratory rate of >60 breaths/min, subcostal or intercostal retractions, nasal flaring, grunting, with or without cyanosis. Results: A total of 320 babies were included in the study with 58.4% male babies and 41.6% female babies. 65% were born by cesarean section and 35% by vaginal delivery. 71.8% babies were born at term and 28.2% babies pre-term. 32.5% had birth weight of <2.5 kg and 67.5% had more than 2.5 kg. 95.62% had a respiratory cause of distress with 60.9% TTN, 27.8% RDS, 6.25% MAS, and 0.62% congenital pneumonia. Only 4.37% cases had a non-respiratory cause with 2.5% sepsis, 1.25% congenital heart disease, and 0.62% congenital diaphragmatic hernia as cause of respiratory distress. Conclusion: 95.62% cases of distress had a respiratory cause with TTN and RDS accounting for a majority of the cases both of which can be easily averted by taking necessary preventive measures by assessing the antenatal risk factors or managed effectively by identifying the cases early on post-partum.